Different forms of nitrogen uptake in tobacco promoted by the arbuscular mycorrhizal fungi - Xie, Yanlan; Song, Xiaohui; Lu, Yingang; Hu, Xianfeng; Pan, Shouhui; Xu, Wei; Xue, Yuan (Frontiers in Plant Science, 2025)
Persistent limitations in nitrogen (N) assimilation efficiency have emerged as a critical constraint in advancing the phytochemical quality of cultivated tobacco (Nicotiana tabacum L.). Arbuscular mycorrhizal fungi (AMF), forming obligate symbiotic associations with over 80% of terrestrial vascular plant species, significantly enhance host plant performance through improved rhizospheric nutrient mobilization. This mutualistic relationship facilitates enhanced acquisition of both macronutrients (particularly phosphorus and N) and water, thereby substantially decreasing agricultural dependence on synthetic fertilizer inputs. Building upon these premises, the present study was carried out to investigate the effects of different forms of nitrogen on the infestation rate and biomass of tobacco plants after inoculation with AMF, as well as the differences in the uptake of different forms of nitrogen by tobacco plants mediated by AMF, using the isotope 15N labelling method. The study revealed significant variations in the uptake of various nitrogen forms by AMF. Under mixed nitrogen source conditions, (NH4)2SO4, KNO3, and glutamine (Glu) constituted 48.61%, 36.10%, and 15.29% of total nitrogen uptake, respectively. Notably, AMF exhibited a preferential uptake hierarchy for NH4+, demonstrating 1.35-fold and 2.94-fold higher absorption rates compared to NO3- and Glu. Furthermore, 15N isotopic tracing analysis confirmed active Glu assimilation by AMF, as evidenced by significantly elevated 15N-Glu uptake in labeled treatments relative to non-labeled controls. These findings collectively suggest that AMF symbiosis modifies tobacco plants’ nutritional preferences among distinct nitrogen forms. This study establishes a theoretical foundation for optimizing nitrogen utilization efficiency and enhancing agronomic productivity in tobacco cultivation systems.